Kompetensi Pedagogik Guru dalam Pengelolaan Pembelajaran Biologi - Ita Ita (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2021)
One of the competencies that must be possessed by a teacher is pedagogic competence. Pedagogic competence is related to the teacher's ability to carry out learning activities. The teacher is an important part in the implementation of the learning process in the classroom. Teachers have a role in preparing lesson plans as well as implementing these plans when managing learning in the classroom. Learning will take place well if the teacher has good pedagogic competence. This study aims to describe the teacher's ability to use the planned biology learning tools. Data collection in this descriptive study was carried out through observation techniques on the learning process for four face-to-face meetings. The research subject is a biology teacher at SMAN 2 Banjarbaru. The teacher is considered to have good competence in applying the biology lesson plan in the classroom seen from the implementation of the initial activity stages, core activities and final activities which show an average score of 3.89 referring to the specified rating scale.